Tanzania : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2004)
This paper reviews the Third Progress Report 2002/03 for Tanzania's Poverty Reduction Strategy. The report highlights what the government did during the past year in terms of policy developments, an assessment of the achievements and challenges, including the monitoring system. There are successes recorded owing to the implementation of the first Poverty Reduction Strategy Paper in macroeconomic performance and in reforms in various areas including the financial sector, public service , and local government. Distinct effort has been made to improve delivery of social services such as education, health, and water.